1993
DOI: 10.1113/jphysiol.1993.sp019843
|View full text |Cite
|
Sign up to set email alerts
|

Human sodium channel myotonia: slowed channel inactivation due to substitutions for a glycine within the III‐IV linker.

Abstract: SUMMARY1. Three families with a form of myotonia (muscle stiffness due to membrane hyperexcitability) clinically distinct from previously classified myotonias were examined. The severity of the disease greatly differed among the families.2. Three dominant point mutations were discovered at the same nucleotide position of the SCN4A gene encoding the adult skeletal muscle Na+ channel asubunit. They predict the substitution of either glutamic acid, valine or alanine for glycine1306, a highly conserved residue wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(132 citation statements)
references
References 19 publications
11
117
0
4
Order By: Relevance
“…Dominant gain-of-function mutations in this gene cause hyperkalemic periodic paralysis (Ptacek et al, 1991), paramyotonia congenita (McClatchey et al, 1992;Ptacek et al, 1992), potassium-aggravated myotonia (Lerche et al, 1993), and hypokalemic periodic paralysis type 2 (Bulman et al, 1999). On the other hand, loss-of-function mutations cause a CMS.…”
Section: Fast-channel Congenital Myasthenic Syndrome (Fccms)mentioning
confidence: 99%
“…Dominant gain-of-function mutations in this gene cause hyperkalemic periodic paralysis (Ptacek et al, 1991), paramyotonia congenita (McClatchey et al, 1992;Ptacek et al, 1992), potassium-aggravated myotonia (Lerche et al, 1993), and hypokalemic periodic paralysis type 2 (Bulman et al, 1999). On the other hand, loss-of-function mutations cause a CMS.…”
Section: Fast-channel Congenital Myasthenic Syndrome (Fccms)mentioning
confidence: 99%
“…Given some of the shared clinical features of hyperkalaemic periodic paralysis and paramyotonia congenita and the recognition of abnormal sodium conductance in both (Lehmann-Horn et al, 1981, 1987a it was proposed and subsequently confirmed that paramyotonia congenita and hyperkalaemic periodic paralysis were allelic disorders (Koch et al, 1991a;Ptacek et al, 1991a, b;Rojas et al, 1991;McClatchey et al, 1992a, b). Later the phenotypes grouped together as the potassium aggravated myotonias were also shown to be sodium channel disorders (Lerche et al, 1993;Ptacek et al, 1994;Ricker et al, 1994) All the skeletal muscle sodium channelopathies are autosomal dominant conditions and de novo mutations can occur. In a proportion of patients with a phenotype typical for paramyotonia congenita no mutation has been identified in SCN4A raising the possibility of further genetic heterogeneity (Miller et al, 2004).…”
Section: Skeletal Muscle Sodium Channelmentioning
confidence: 99%
“…This phenotype was classified as myotonia fluctuans (Ricker et al, 1990(Ricker et al, , 1994Lennox et al, 1992). The term myotonia permanens was introduced to describe patients with a third clinical variant characterized by very severe persistent myotonia which significantly impaired respiration (McClatchey et al, 1992b;Lerche et al, 1993). These three purely myotonic disorders shared the potassium aggravation and the absence of sensitivity to cold.…”
Section: Sodium Channel Myotoniamentioning
confidence: 99%
“…Gain-of-function mutations in SCN4A, the gene encoding the pore-forming alpha (α) subunit of the human skeletal muscle voltage-gated Na + channel type IV (hNa v 1.4) have been associated with non-dystrophic skeletal muscle pathologies including paramyotonia congenita, 1 hyperkalaemic periodic paralysis, 2 and potassium-aggravated myotonia 3 (reviewed in refs. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%